El proceso de socialización de los niños y niñas achuar de 2 a 6 años de edad : estudio de caso en las comunidades Nases, Suritiak, Jikiamat y Wasakentsa - Wisum Semu, Kaasap Bartolome (2018)
The present case study focused on discovering how children are socialized in centers in the Achuar family. At the beginning of the work it was assumed that all the children reached the same level of socialization. However, a few differences have been found in each center. Among the four communities investigated (Jiamat, Nases, Suritiak and Wasakentsa) parents have their way of socializing and teaching their children, for example, in the two Nases and Suritiak communities, when we attend the foundation festivals, the parents themselves They stopped the children and asked them to go home. Later, there was an opportunity to talk with the parents to ask them to let the children participate in the programs. In these communities, it was observed that children are shy and afraid to talk with strangers. This shyness, it seems, appears due to the influence of family education. Unlike the two Nases and Suritiak communities, in Wasak'entsa and Jikiamat, parents and children have a different socialization. Between the two communities live the Salesian Fathers, the teachers, the doctors, the Marianite sisters. Then, the children's participation is free and it is also evident in the children who are more extroverted and are not afraid to interact with adults. Finally, it has been discovered that all children are equal in learning, and are in constant discovery.